Nisin-preconditioned mesenchymal stem cells combatting nosocomial Pseudomonas infections - Sara Enayati; Raheleh Halabian; Parvaneh Saffarian; Hossein Aghamollaei; Pardis Saeedi (Regenerative Therapy)
Background: Nosocomial infections caused by multidrug-resistant Pseudomonas aeruginosa are a considerable public health threat, requiring innovative therapeutic approaches. Objectives: This study explored preconditioning mesenchymal stem cells (MSCs) with the antimicrobial peptide Nisin to enhance their antibacterial properties while maintaining regenerative capacity. Methods: Human MSCs were preconditioned with varying concentrations of Nisin (0.1–1000 IU/mL) to determine an optimal dose. MSCs preconditioned with Nisin were characterized using microscopy, flow cytometry, gene expression analysis, and functional assays. The effects of preconditioning on the viability, phenotype, differentiation capacity, antimicrobial peptide expression, and antibacterial activity of MSCs against Pseudomonas aeruginosa were tested in vitro. The therapeutic efficacy was evaluated by topically applying conditioned media from Nisin-preconditioned versus control MSCs to infected wounds in a rat model, assessing bacterial burden, healing, host response, and survival. Results: An optimal Nisin dose of 500 IU/mL was identified, which increased MSC antibacterial gene expression and secretome activity without compromising viability or stemness. Nisin-preconditioned MSCs showed upregulated expression of LL37 and hepcidin. Conditioned media from Nisin-preconditioned MSCs exhibited about 4-fold more inhibition of P. aeruginosa growth compared to non-preconditioned MSCs. In the wound infection model, the secretome of Nisin-preconditioned MSCs suppressed bacterial load, accelerated wound closure, modulated inflammation, and improved survival compared to standard MSC treatments. Conclusion: This study explores the effect of preconditioning MSCs with the antimicrobial peptide Nisin on enhancing their antibacterial properties while maintaining regenerative capacity. Secreted factors from Nisin-preconditioned MSCs have the potential to attenuate infections and promote healing in vivo. The approach holds translational promise for managing antibiotic-resistant infections and warrants further development. Preconditioned MSCs with Nisin may offer innovative, multifaceted therapies for combating nosocomial pathogens and promoting tissue regeneration.